Analysing theatre audio introductions: lexical complexity, gender bias in personal characteristics description and structural elements - Secară, Alina; Chereji, Raluca (The Journal of Specialised Translation, 2023)
Starting from the premise that language choices reflect underlying beliefs and assumptions and offer a mirror reflecting attitudes and potential biases present in wider society, the current article provides a linguistic analysis of 52 English audio introductions produced by five UK professional audio describers for a UK-based theatre. We investigate the extent to which the gender of the described characters plays a role in the linguistic choices describers make when describing visible physical markers such as age and race, or abilities and social status. For this purpose, we propose and use a new corpus-based framework for the analysis of personal characteristics in audio introductions. We enrich these results with an analysis of the language complexity of audio introduction texts in terms of their readability and lexical diversity by applying dedicated linguistic investigation metrics. Our results show varying levels of linguistic complexity consistent with the audience profile and play genre, as well as imbalances in the description of characters’ personal characteristics depending on their gender. We also confirm previous findings which highlight a degree of standardisation inherent in audio introductions in terms of structural elements present, and their order of appearance, despite the lack of predefined templates.